Enzyme Biocatalysis Principles and Applications - Illanes, Andrés; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2008)
This book was written with the purpose of providing a sound basis for the design of enzymatic reactions based on kinetic principles, but also to give an updated vision of the potentials and limitations of biocatalysis, especially with respect to recent app- cations in processes of organic synthesis. The ?rst ?ve chapters are structured in the form of a textbook, going from the basic principles of enzyme structure and fu- tion to reactor design for homogeneous systems with soluble enzymes and hete- geneous systems with immobilized enzymes. The last chapter of the book is divided into six sections that represent illustrative case studies of biocatalytic processes of industrial relevance or potential, written by experts in the respective ?elds. We sincerely hope that this book will represent an element in the toolbox of gr- uate students in applied biology and chemical and biochemical engineering and also of undergraduate students with formal training in organic chemistry, biochemistry, thermodynamics and chemical reaction kinetics. Beyond that, the book pretends also to illustrate the potential of biocatalytic processes with case studies in the ?eld of organic synthesis, which we hope will be of interest for the academia and prof- sionals involved in R&D&I. If some of our young readers are encouraged to engage or persevere in their work in biocatalysis this will certainly be our more precious reward.
Keywords: Biochemical engineering; Catalysis; Biotechnology; Microbiology; Chemical engineering; Biochemical Engineering; Catalysis; Biotechnology; Applied Microbiology; Industrial Chemistry/Chemical Engineering